Modified Photobioreactor for Biofixation of Carbon Dioxide by Chlorella vulgaris at Different Light Intensities - Naderi, G.; Tade, Moses; Znad, H. (Wiley-VCH Verlag, 2015)
The performance of a modified bioreactor inside a light enclosure for carbon dioxide biofixation by Chlorella vulgaris was investigated. The influence of different light intensities on the CO2 biofixation and biomass production rates was evaluated. The results showed that the photon flux available to the microalgal cultures can be a key issue in optimizing the microalgae photobioreactor performance, particularly at high cell concentrations. Although the optimal pH values for C. vulgaris are in the range of 6–8, cell growth can take place even at pH 4 and 10. Batch microalgae cultivation in the photobioreactor was used to investigate the effect of different light intensities. The maximum biomass concentration of 1.83 g L−1 was obtained at a light intensity of 100 μmol m−2s−1 and under aeration with 2 L min−1 of 2 % CO2-enriched air.